Spatial and Temporal Assessment of Water Quality in the Bektiharjo River, Tuban Regency, Using the Water Quality Index and GIS-Based QUAL2Kw Modeling (2021-2025) - Fadhillah Zahrotul Jannah; Maritha Nilam Kusuma (PT. Global Research Collaboration, 2026)
The Bektiharjo River is an important water resource supporting domestic, agricultural, tourism, and ecological activities in Tuban Regency, Indonesia. Increasing anthropogenic activities have raised concerns regarding water quality degradation. This study aimed to evaluate the spatial and temporal characteristics of the Bektiharjo River during 2021-2025 by integrating the Water Quality Index (WQI), Geographic Information Systems (GIS), and the QUAL2Kw model. Secondary water quality data, including pH, TSS, DO, BOD, COD, nitrate, phosphate, and fecal coliform, were analyzed using WQI, spatial mapping, and water quality simulation under existing and critical flow conditions. The results showed that water quality declined from upstream to downstream, with average WQI values of 54-56 in the upstream segment, 48-52 in the middle segment, and 48-50 in the downstream segment, showing moderate to poor water quality. Seasonal differences were relatively small, with WQI varying by only 2-4 points across river segments. Water quality was generally higher during the rainy season in the upstream and middle reaches, whereas the downstream reach showed a slightly higher WQI during the dry season. QUAL2Kw calibration produced relative errors below 5%, showing good agreement between simulated and observed values during model calibration; however, these results represent calibration performance rather than independent model validation. Under existing conditions, DO decreased from 6.60 to 6.16 mg/L, while BOD increased from 0.89 to 2.50 mg/L from upstream to downstream. Under critical low-flow conditions, DO declined further to 4.12 mg/L, whereas BOD increased to 3.74 mg/L, showing reduced self-purification capacity. The findings show that management efforts should prioritize upstream watershed conservation, environmentally friendly agricultural practices in the middle reach, and improved domestic wastewater management in the downstream reach to support sustainable river management.